Agriculture and citadel in the Bronze Age Aegean: the view from western Anatolia - Maltas, T (2021)
This project aims to assess how agricultural production was adapted to the changing social and economic environments of Late Chalcolithic to Late Bronze Age western Anatolia. In doing so, it aims to suggest how arable farming contributed to the formation and collapse of elite social and economic structures within the citadel and lower town settlements of the Early Bronze Age (EB/EBA) II-III. This is achieved through a suite of analyses conducted on archaeobotanical assemblages from four sites in the Izmir region of western Anatolia: Liman Tepe, Bakla Tepe, Kocabaş Tepe and Çeşme-Bağlararası. In particular, stable isotope analysis of crop remains and functional ecological analysis of their associated weeds are used to establish crop husbandry and arable land management practices. These data are synthesised with archaeological evidence for the social morphology of settlements to provide insights into the organisation of the agricultural economy. They are also interpreted with reference to the climatic and ecological contexts of agricultural production.